Interactions between propagating rotational rifts and linear rheological heterogeneities: Insights from three‐dimensional laboratory experiments. Issue 3 (14th March 2017) - Molnar, N. E.; Cruden, A. R.; Betts, P. G.
Abstract: The lateral propagation of rifts is a consequence of the relative divergence of lithospheric plates about a pole of rotation. Modern and ancient examples of rifts are known to overprint preexisting linear anisotropies in the crust and lithosphere, such as lithospheric boundaries, crustal sutures, and thermal anomalies. Here we investigate how propagating rifts interact with preexisting structures by using three‐dimensional analogue experiments with rotational extensional boundary conditions and variably oriented linear weak zones in the lithospheric mantle. When linear weaknesses are oriented at low angles to the rift axis, early strain localization occurs in narrow domains, which merge at later stages, resulting in continental breakup by unzipping. Strong strain partitioning is observed when the linear heterogeneity is oriented at high angles with respect to the rift axis. In these experiments, early subparallel V‐shaped basins propagate toward the pole of rotation until they are abandoned and strain is transferred entirely to structures developed in the vicinity of the strongly oblique weak lithosphere zone boundary. The experimental results are characterized in terms of their evolution, patterns of strain localization, and surface topography as a function of the lithospheric heterogeneity obliquity angle. Comparison of the experiments to ancient and modern examples in nature may help to elucidate the common but still poorly understood process of propagating rift‐lithospheric heterogeneity interaction. Key Points: New analogue experiments of rotational extension explore how rifts propagate into lithospheres with variably oriented linear weak zones Modes of deformation are classified as a function of the orientation of linear weak zones with respect to the rift axis Inherited structures and changes in the extension direction over time should be investigated jointly to understand how rifts propagate